The Diverse Iron Distribution in Eudicotyledoneae Seeds: From Arabidopsis to Quinoa - Ibeas, Miguel Angel; Grant-Grant, Susana; Coronas, Maria Fernanda; Vargas-Pérez, Joaquín Ignacio; Navarro, Nathalia; Abreu, Isidro; Castillo-Michel, Hiram; Avalos-Cembrano, Natalia; Paez Valencia, Julio; Perez, Fernanda; González-Guerrero, Manuel; Roschzttardtz, Hannetz (Frontiers in Plant Science, 2019)
Seeds accumulate iron during embryo maturation stages of embryogenesis. Using Arabidopsis thaliana as model plant, it has been described that mature embryos accumulate iron within a specific cell layer, the endodermis. This distribution pattern was conserved in most of the analyzed members from Brassicales, with the exception of the basal Vasconcellea pubescens that also showed elevated amounts of iron in cortex cells. To determine whether the V. pubescens iron distribution was indicative of a wider pattern in non-Brassicales Eudicotyledoneae, we studied iron distribution pattern in different embryos belonging to plant species from different Orders from Eudicotyledoneae and one basal from Magnoliidae. The results obtained indicate that iron distribution in A. thaliana embryo is an extreme case of apomorphic character found in Brassicales, not-extensive to the rest of Eudicotyledoneae.